2015
DOI: 10.3892/or.2015.3891
|View full text |Cite
|
Sign up to set email alerts
|

Icariin regulates the proliferation and apoptosis of human ovarian cancer cells through microRNA-21 by targeting PTEN, RECK and Bcl-2

Abstract: Icariin is the main active ingredient found in the traditional Chinese medicinal plant Epimedium, and exhibits various pharmacological effects such as enhanced immune function, anticancer activity, improved cardiovascular function and endocrine adjustment. However, the effect of icariin on ovarian cancer and the related mechanism have never been investigated. In the present study, we aimed to verify whether icariin inhibits the proliferation and increases the apoptosis of human ovarian cancer cells, and its mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 35 publications
1
58
1
Order By: Relevance
“…MiR-21 is highly expressed in multiple cancers, such as epithelial cell cancer, connective tissue cancer, hematopoietic cell cancer, reproductive cell cancer and nerve cell cancer [9]. Previous studies have demonstrated that the target genes of miR-21 including phosphatase and tensin homolog detected on chromosome 10 (PTEN), Bcl-2 , TPM1 and PDCD4 which are cancer suppressed genes [1013]. Previous studies have shown that miR-21 regulates PTEN by interacting with its target gene 3′-UTR and participates in the process of cancer occurrence and development [1415].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-21 is highly expressed in multiple cancers, such as epithelial cell cancer, connective tissue cancer, hematopoietic cell cancer, reproductive cell cancer and nerve cell cancer [9]. Previous studies have demonstrated that the target genes of miR-21 including phosphatase and tensin homolog detected on chromosome 10 (PTEN), Bcl-2 , TPM1 and PDCD4 which are cancer suppressed genes [1013]. Previous studies have shown that miR-21 regulates PTEN by interacting with its target gene 3′-UTR and participates in the process of cancer occurrence and development [1415].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li et al . 39 demonstrated that iicarin, an active ingredient of the Chinese medicinal plant Epimedium regulates proliferation and apoptosis of human ovarian cancer cells by targeting miR-21 and substantially increasing RECK protein expression. Curcumin was shown to inhibit the growth of oesophageal cancer cell lines by inhibiting Notch signaling and Notch-specific miR-21 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus there is a feedback loop between RECK, STAT3 and MMPs, suggesting the up-expression of the tumor suppressor RECK may influence the signal transduction of STAT3 and MMPs. Notably, several previous studies reported that up-regulation of RECK resulted in decreased ovarian cancer amplification [14]. In addition, histone deacetylase inhibitor inhibited ovarian cancer cell migration partially through up-regulation of RECK [15].…”
Section: Introductionmentioning
confidence: 99%